2021
DOI: 10.1590/0100-3984.2020.0039
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the cranial nerves in congenital, traumatic, and vascular diseases: a pictorial essay

Abstract: The cranial nerves, which represent extensions of the functional structures of the brain, traverse the head and neck. They are connected to various cranial structures and are associated with several diseases. An in-depth understanding of their complex anatomy and normal imaging appearance allows the examiner to identify and characterize abnormalities with greater precision. One important tool for evaluating the cranial nerves is contrast-enhanced magnetic resonance imaging, especially three-dimensional steady-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…The fourth nerve arises from the dorsal surface of the midbrain just below the inferior colliculus, surrounds the contralateral surface of the midbrain, passes along the lateral wall of the cavernous sinus and through the superior orbital fissure, and innervates the superior oblique muscles. Lastly, the sixth nerve arises from the pontomedullary junction near the midline, crosses the petrous apex within Dorello's canal, ascends to pass through the cavernous sinus near internal carotid arteries, exits through the superior orbital fissure, and innervates the lateral rectus muscle [14].…”
Section: Introductionmentioning
confidence: 99%
“…The fourth nerve arises from the dorsal surface of the midbrain just below the inferior colliculus, surrounds the contralateral surface of the midbrain, passes along the lateral wall of the cavernous sinus and through the superior orbital fissure, and innervates the superior oblique muscles. Lastly, the sixth nerve arises from the pontomedullary junction near the midline, crosses the petrous apex within Dorello's canal, ascends to pass through the cavernous sinus near internal carotid arteries, exits through the superior orbital fissure, and innervates the lateral rectus muscle [14].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous article (1) , we reviewed congenital, traumatic, and vascular diseases of the cranial nerves. This pictorial essay goes further, illustrating infectious, neo-plastic, and demyelinating diseases, as well as other inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…MRI showed that in the present case the lesion mimicked a glioblastoma. Tumors are exhibit relatively high signal intensity and restricted diffusion 5,6,7,11 , which is common in CNS lymphoma 12 and GBM (except in necrotic areas). In general, the detection of hypoperfusion on MRI, as observed in this case, is fundamental for the accurate preoperative diagnosis of lymphoma 2,6,7,13,14,15,16. The elevated risk for many cancers, especially after the onset of acquired immunodeficiency syndrome, highlights the contribution of immunosuppression to the frequency of cancer in this population, although a decline in this frequency has been observed with adequate modern antiretroviral therapy 17 .…”
Section: Introductionmentioning
confidence: 99%